Whose Knowledge Counts? Decolonial and Anticolonial Reckonings in STEM Education - Gyamerah, Kenneth (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación, 2025)
Globally, science, technology, engineering, and mathematics (STEM) education is widely framed as essential to innovation, economic growth, and social progress. These framings, however, often overlook STEM’s long-standing connections to colonialism, empire, and the exclusion of certain forms of knowledge. Decolonial and anticolonial perspectives are used to examine the assumptions about knowledge and reality that shape STEM education. While STEM education has played an important role in scientific and technological development, it has also reinforced hierarchies that marginalize Black, Indigenous, and other non-Western scientific traditions. These hierarchies persist through curriculum design, ideas about ability, language dominance, and universalist practices that treat Euro-Western science as neutral and authoritative. Bringing decoloniality and anticoloniality into conversation makes visible how STEM education has helped sustain exclusionary knowledge systems and colonial ways of knowing. Four recurring myths are identified that continue to structure STEM education and limit possibilities for meaningful change. Rethinking STEM education along these lines is necessary to support epistemic justice and to open space for more plural, relational, and equitable futures.